2019 Computing in Cardiology Conference (CinC) 2019
DOI: 10.22489/cinc.2019.313
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Technology: Signal Recovery of Electrocardiogram from Short Spaced Leads in the Far-field Using Discrete Wavelet Transform Based Techniques

Abstract: Bipolar ECG leads recorded from closely spaced electrodes are challenging in any context. When they are positioned distally with respect to the source field (far-field), the recovery of clinically useful signal content represents an even greater challenge. Due to the increased interest in ambulatory wellness devices, particularly wrist-worn devices, there is a renewed interest in recovering ECG signals from distally located bipolar leads. In this study 10 bipolar leads were simultaneously recorded at various l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…The results from this study may be contrasted with the findings in a previous study carried out on a pilot patient database (N = 11) [ 27 ]. There, prior to QRS detection performance analysis with the PT algorithm, arm-ECG signal denoising was successfully achieved by an advanced Discrete Wavelet Transforms (DWT) ECG filtering technique using a 4th-order wavelet decomposition, with the db4 Daubechies wavelet as the mother wavelet.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…The results from this study may be contrasted with the findings in a previous study carried out on a pilot patient database (N = 11) [ 27 ]. There, prior to QRS detection performance analysis with the PT algorithm, arm-ECG signal denoising was successfully achieved by an advanced Discrete Wavelet Transforms (DWT) ECG filtering technique using a 4th-order wavelet decomposition, with the db4 Daubechies wavelet as the mother wavelet.…”
Section: Discussioncontrasting
confidence: 84%
“…There, prior to QRS detection performance analysis with the PT algorithm, arm-ECG signal denoising was successfully achieved by an advanced Discrete Wavelet Transforms (DWT) ECG filtering technique using a 4th-order wavelet decomposition, with the db4 Daubechies wavelet as the mother wavelet. Then, the performance analysis results [ 27 ] indicated that the bipolar lead on the upper-arm, defined as Ch8 − Ch10, presented the best sensitivity mean value (99.8%) and mean PPV (98.4%) performance. In contrast, the performance results obtained here indicated a maximum sensitivity mean value of 86.8% (with arm Lead-1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations